A rare cause of stroke in young children: minor head trauma associated with mineralising lenticulostriate angiopathy in three patients. (3rd April 2022) - Sugumar, Kiruthiga; Chidambaram, Aakash Chandran; Deepthi, Bobbity; Krishnamurthy, Sriram; Delhikumar, C. G.
ABSTRACT: Acute basal ganglia infarct following minor head trauma in association with mineralisation of lenticulostriate arteries is an increasingly recognised entity in childhood stroke. Three cases with a classical history and phenotypical features of mineralising angiopathy are described. Case 1 was a 2-year-old girl who presented with acute onset hemiparesis with a same-side upper motor neuron (UMN)-type facial palsy following minor head trauma. Case 2 was a 14-month-old boy who presented with a left side hemiparesis and a left UMN-type facial nerve palsy following a minor fall. Case 3 was an 8-month-old boy who, following a fall from his cot, had a sudden-onset hemiparesis on the right side and deviation of the angle of the mouth to the left. In brain computed tomography, all three cases demonstrated characteristic basal ganglia calcification of the mineralising angiopathy. Magnetic resonance imaging of the brain demonstrated features supportive of acute infarcts in the lentiform nucleus, caudate nucleus and putamen. Two of the patients had iron deficiency anaemia with haemoglobin of 7.0 g/dL and 7.8 g/dL, respectively. On follow-up, Case 1 had mild residual weakness and the other two made a complete recovery. None of the patients had a recurrence of stroke. Basal ganglia stroke with mineralising angiopathy should be considered in toddlers presenting with sudden-onset focal neurological deficits preceded by minor head trauma. Abbreviations: ADC: apparent diffusion coefficient; CT: computed tomography; DWI: diffusion-weighted imaging; Hb: haemoglobin; IDA: iron deficiency anaemia; MRI: magnetic resonance imaging; SLV: sonographic lenticulostriate vasculopathy; SWI: susceptibility weighted imaging; UMN: upper motor neuron.